Tracing the Cenozoic Southern Patagonian Andes growth (51°15” S-53°39” S) from the integrated study of the orogen-foreland basin pair - Rivera Rosado, Huber Alberto (HAL CCSD, 2022)
Comprehensive knowledge on the tempo and style of shortening, exhumation, and sedimentary evolution of the Southern Patagonian Andes and its related Magallanes-Austral foreland basin have remained elusive. Throughout the history of the Southern Patagonian Andes three approaches and collisions of spreading ridges, periods of tectonic erosion, and possible subduction flat-slab events have interacted with the continental margin. Moreover, the opening of the oceanic Drake Passage (i.e., the opening of the Scotia Sea) between the Antarctic Peninsula and South America and the overall Cenozoic reorganization of the tectonic plates setting and kinematic, certainly positions this Andean segment as one of the most complexes. Notwithstanding, the southern Patagonian Andes and its Magallanes-Austral foreland basin offer a unique opportunity to evaluate how and to what extent the changing geodynamic setting control the development and evolution of an Andean-type orogen foreland basin pair. In this research proposal I will envisage the Magallanes fold and thrust belt (orogenic wedge) and the Magallanes Austral foreland basin (51°15”S-53°39”S) as an integrated orogen foreland basin pair where combine both the geometry, evolution and filling pattern of the syntectonic sedimentary basin with the kinematics constraint of the adjacent mountain belt to understand the evolutionary stages of this Cordilleran system and to discriminate between the different processes that controlled the geodynamic evolution of this part of the Andes: crustal thickening related to tectonic shortening, dynamic topography related to the subduction processes, interactions between climatic and tectonic changes, among others. The intermediate position of the study area (between 2 main structural regimes: compression and transpression) and complete latest Cretaceous-Cenozoic stratigraphy will give insights into the contribution of the contractional versus transpressional dominated processes and will provide reliable and accurate answers regarding if the ...